Pemberdayaan UMKM Berbasis Kearifan Lokal melalui Pendampingan dan Pelatihan Produk Keripik Pepaya di Desa Montorna Kecamatan Pasongsongan - Subqi, Tajus; Rizqiyah, Amilatur; Putri, Kanza Nabilah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Empowerment of Micro, Small and Medium Enterprises (MSMEs) is the main key in improving the village economy in Indonesia. In Montorna Village, Pasongsongan District, Sumenep Regency, MSMEs have great potential to boost community welfare. Papaya is the one of fruits that grows in tropical areas including in Montorna Village. as fruit that has great potential to be raw material in processing products with high sell value, papaya chips can become one of product that can be developed, not only as popular snack but also it has widely marketed opportunities. In this method, we are as researcher doing assistance by using the PAR method. In the PAR method, researcher takes the KUPAR cycle, namely knowing, understanding, planning, acting and reflecting. The purposes of this this stage is to understand many issues that relevant with empowerment of MSMEs and the potential of local society. With training and mentoring program, local society can get many knowledge and skill that needed to manage their bussines efficiently. With this, researcher hopes MSMEs in Montana village can become main booster in increasing of quality society life and creat a new employment that can give great contribution in economic growth inclusively and sustainable.